Regional Development Of Municipalities With A Population Of 10 To 30 Thousand In The North-Eastern And South-Eastern Planning Regions Of Bulgaria - Petrov, Kamen; Tsonkov, Nikolay; Slaveva, Krasimira (Journal of Ecohumanism, 2024)
This article is devoted to assessing and analyzing the development of municipalities from 10 to 30 thousand people in the Bulgarian Northeast and Southeast regions on level 2. At the beginning, a characterization of the ongoing processes and the importance of the regionalization process for the spatial development of individual territories is presented, the purpose of the article is formed, and the leading task is to make a statistical analysis of leading socio-ideographic indicators that bring to the fore the characteristics of these territorial units and present to our attention their state. It is important to be able, based on the assessment of the situation and the reference to expert assessment, to take the appropriate measures and sets of actions to promote the regional economic development of these municipalities. Comparing municipalities in these two regions, the southwest and south-central areas of the country emerge as the richest and most developed regions regarding household income, techno-social equipment, and endowed and economic potential. The analyses revealed several detailed aspects of the typology of problems specific to the various municipalities, which can be examined in more detail in another study. The conclusion draws relevant recommendations for improving regional development in these territories.